It's a woman's world a century of women's voices in poetry - Philip, Neil. (New York Dutton Children's Books, 2000)
An anthology of poetry by twentieth-century women from around the world including, Sylvia Plath, Nigar Hanim, Sonia Sanchez, and Nellie Wong.
UCWS-2014-G-1941 donated by Prof. Eric Julian Manalastas
Keywords: Children's poetry -- Women authors; Children's poetry -- Women authors -- Translations into English; Women -- Juvenile poetry; Poetry -- Collections; Women -- Poetry